PACKAGING DESIGN IN INCREASING THE VALUE ADDED OF HONEY OF COFFEE FLOWER AS A REGIONAL PRIME PRODUCT - Yessy Rosalina; Alnopri Alnopri; Prasetyo Prasetyo (BPFP Faperta UNIB, 2012)
Pure honey has a good nutrient content and it is also believed it has healthy peculiar property. Coffee plants are one of the plants that are good in honey bees breeding. Honey which is produced from the nectar of coffee flower price selling is relatively high. In order to increase the value added of honey of coffee flower, the researchers in package design were needed to get the best one. The aim of this study was to determine the influence of image and packaging design either simultaneously or partially into purchasing decisions of pure honey consumers. Based on this research, it is known that an ideal packaging material for honey of coffee flower is a bottle compared to flexible packaging. The reason is functional: the bottle packaging is capable to fulfill its function as an efficient and effective packaging. In graphic design, the packaging of pure honey that preferred by the panelists is the packaging that has more colors contrast between its base colors and layout of the flower of coffee whereas the size of a font is already good because it is clearly legible.